Characterization of SCF-Complex during Bovine Preimplantation Development - Benesova, Veronika; Kinterova, Veronika; Kanka, Jiri; Toralova, Tereza (PloS one, 2016)
The degradation of maternal proteins is one of the most important events during early development, and it is presumed to be essential for embryonic genome activation (EGA), but the precise mechanism is still not known. It is thought that a large proportion of the degradation of maternal proteins is mediated by the ubiquitin-proteolytic system. In this study we focused on the expression of the Skp1-Cullin1-F-box (SCF) complex, a modular RING-type E3 ubiquitin-ligase, during bovine preimplantation development. The complex consists of three invariable components--Cul1, Skp1, Rbx1 and F-box protein, which determines the substrate specificity. The protein level and mRNA expression of all three invariable members were determined. Cul1 and Skp1 mRNA synthesis was activated at early embryonic stages, at the 4c and early 8c stage, respectively, which suggests that these transcripts are necessary for preparing the embryo for EGA. CUL1 protein level increased from MII to the morula stage, with a significant difference between MII and L8c, and between MII and the morula. The CUL1 protein was localized primarily to nuclei and to a lesser extent to the cytoplasm, with a lower signal in the inner cell mass (ICM) compared to the trophectoderm (TE) at the blastocyst stage. The level of SKP1 protein significantly increased from MII oocytes to 4c embryos, but then significantly decreased again. The localization of the SKP1 protein was analysed throughout the cell and similarly to CUL1 at the blastocyst stage, the staining was less intensive in the ICM. There were no statistical differences in RBX1 protein level and localization. The active SCF-complex, which is determined by the interaction of Cul1 and Skp1, was found throughout the whole embryo during preimplantation development, but there was a difference at the blastocyst stage, which exhibits a much stronger signal in the TE than in the ICM. These results suggest that all these genes could play an important role during preimplantation development. This paper reveals comprehensive expression profile, the basic but important knowledge necessary for further studying.
Keywords: Cattle; RNA, Messenger; blastocysta; Male; oocyty; vývojová regulace genové exprese; skot; Transcription, Genetic; Embryonic Development; Gene Expression Regulation, Developmental; F-Box Proteins; signální transdukce; kulinové proteiny; Spermatozoa; zinkové prsty; mužské pohlaví; proteiny asociované s kinázou S-fáze; SKP Cullin F-Box Protein Ligases; proteinligasy komplexu SCF; Signal Transduction; Fertilization in Vitro; fertilizace in vitro; genetická transkripce; substrátová specifita; F-box proteiny; Animals; S-Phase Kinase-Associated Proteins; Zinc Fingers; ženské pohlaví; Substrate Specificity; zvířata; Cullin Proteins; embryonální vývoj; spermie; Female; Blastocyst; messenger RNA; Oocytes